2015
DOI: 10.15302/j-fase-2015050
|View full text |Cite
|
Sign up to set email alerts
|

Review of the direct thermochemical conversion of lignocellulosic biomass for liquid fuels

Abstract: Increased demand for liquid transportation fuels, environmental concerns and depletion of petroleum resources requires the development of efficient conversion technologies for production of second-generation biofuels from non-food resources. Thermochemical approaches hold great potential for conversion of lignocellulosic biomass into liquid fuels. Direct thermochemical processes convert biomass into liquid fuels in one step using heat and catalysts and have many advantages over indirect and biological processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…These are applied for a range of unit operation applications, including heat exchangers, distillation columns, reactors, fermentors, furnaces, etc. A number of additional reviews with a similar scope have been published in recent years, of which the summary becomes redundant, because the authors cover a number of overlapping areas of research, with major contributions from Bridgewater et al, 51−54 Di Blasi, 55 Butler et al, 56 Carpenter et al, 57 Dickerson et al, 58 Jiang et al, 59 Sharma et al, 60 Anca-Couce, 43 Mostafazadeh et al, 61 and Hameed et al 62 The ability to separate the carbohydrate fractions from the solid biomass and the relatively simple and uniform structure of these polymers have attracted the most research attention over the years for pyrolysis of cellulose and its sugar constituents. 46,51,52 Although this field has been studied for decades, a number of unanswered questions remain regarding the fundamental elementary mechanisms of product formation in the condensed and gas phase reactions.…”
Section: Mechanism and Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are applied for a range of unit operation applications, including heat exchangers, distillation columns, reactors, fermentors, furnaces, etc. A number of additional reviews with a similar scope have been published in recent years, of which the summary becomes redundant, because the authors cover a number of overlapping areas of research, with major contributions from Bridgewater et al, 51−54 Di Blasi, 55 Butler et al, 56 Carpenter et al, 57 Dickerson et al, 58 Jiang et al, 59 Sharma et al, 60 Anca-Couce, 43 Mostafazadeh et al, 61 and Hameed et al 62 The ability to separate the carbohydrate fractions from the solid biomass and the relatively simple and uniform structure of these polymers have attracted the most research attention over the years for pyrolysis of cellulose and its sugar constituents. 46,51,52 Although this field has been studied for decades, a number of unanswered questions remain regarding the fundamental elementary mechanisms of product formation in the condensed and gas phase reactions.…”
Section: Mechanism and Kineticsmentioning
confidence: 99%
“…These are applied for a range of unit operation applications, including heat exchangers, distillation columns, reactors, fermentors, furnaces, etc. A number of additional reviews with a similar scope have been published in recent years, of which the summary becomes redundant, because the authors cover a number of overlapping areas of research, with major contributions from Bridgewater et al, Di Blasi, Butler et al, Carpenter et al, Dickerson et al, Jiang et al, Sharma et al, Anca-Couce, Mostafazadeh et al, and Hameed et al…”
Section: Mechanism and Kineticsmentioning
confidence: 99%
“…Many studies devoted to this field can be found in the literature, focusing on green alternatives to conventional fuels and chemicals. These works reported on possible conversion methods to produce hydrocarbons (typically liquid fuels) from renewable materials. …”
Section: Introductionmentioning
confidence: 99%
“…Different types of reactors have been used to conduct pyrolysis reactions over time [11]. The more common ones are: ablative, conical spouted bed, rotating cone, Auger and fluidised bed (bubbling and circulating) reactors [12][13][14]. Lam et al [15] state that most studies pertaining to biomass pyrolysis at the laboratory scale are performed in batch reactors as the latter are simple to use, no high-pressure pump or compressor is needed, all types of biomass can be used and no complex separation means needs to be applied to recover the remaining bio-char.…”
Section: Pyrolysis and Catalytic Pyrolysismentioning
confidence: 99%